Effect of Adding Jackfruit Dami (Artocarpus heterophyllus) on the Sensory and Chemical Characteristics of Red Dragon Fruit (Hylocereus polyrhizus) Fruit Leather - Putri, Ananda Ericka; Murhadi, Murhadi; Herdiana, Novita; Hidayati, Sri (Universitas Brawijaya, 2024)
This research explores how the use of jackfruit mesocarp waste can improve the sensory and chemical aspects of red dragon fruit skin, considering the high pectin and fiber content in jackfruit dami, despite its lack of taste and color. Red dragon fruit is added to compensate for this deficiency. The research used a Completely Randomized Block Design with five comparisons of red dragon fruit and jackfruit dami: 100% : 0%, 75% : 25%, 50% : 50%, 2% : 75%, and 0% : 100%, each tested in five repetitions. The analysis carried out included testing data homogeneity with the Bartlett test, followed by the Tuckey range test, analysis of variance, and the Honest Significant Difference Test (HSD) at a significance level of 5%. This study concluded that the proportion of jackfruit dami significantly influences the sensory (texture, color, aroma, taste, and overall liking) and chemical properties (moisture content, ash content, acidity, vitamin C, and reducing sugars) of the fruit skin. The optimal composition found was a 50:50 mixture of dami jackfruit and red dragon fruit, which produced the desired sensory characteristics (a texture value of 3.87 indicated very elastic, a color value of 3.55 indicated a red color, an aroma value of 3.24 indicated favorable, taste value of 3.11, and overall preference rating of 3.60) and good chemical properties (moisture content 14.09%, ash content 0.88%, pH 4.26, vitamin C content 1.11 mg/g, and reducing sugar content 23.73%).